A plasmid containing CpG ODN as vaccine adjuvant against grass carp reovirus in grass carp Ctenopharyngodon idella - Su, Hang (Oncotarget, 2017)
CpG oligodeoxynucleotides (ODNs) are proved to have strong immune stimulatory activity. Plasmids containing CpG ODNs could be conveniently and low-costly used as vaccine adjuvant. However, they are different among various plasmids, motif repeats, species, etc. In the present study, plasmid pcDNA3.1 (+) containing five repetitions of CpG ODN 1670A named pcDNA3.1-1670A*5 with strong immunostimulation was screened out from twelve recombinant plasmids and three empty vectors by cell proliferation activity, interferon promoter activities and immune related gene expressions in CIK cells. It works through TLR9-mediated signaling pathway, triggering the immune related genes expression. Furthermore, the potentiality of pcDNA3.1-1670A*5 as adjuvant was tested in vivo. pcDNA3.1-1670A*5 was co-inoculated with inactivated GCRV vaccine on grass carp fingerlings. Immunoglobulins (IgM, IgD, IgZ), TLR9, IFNγ2, IFN1, TNF-α, Mx2 and VP4 were examined. Ultimately, pcDNA3.1-1670A*5 significantly enhanced the expressions of IgM in serum, head kidney and spleen, recognition receptor TLR9 as well as antiviral effector molecule Mx2, and inhibited GCRV proliferation in head kidney and spleen tissues. The present study explored the application and mechanism of plasmid containing CpG ODN as high-efficient adjuvant to promote efficiency of vaccine and control disease in grass carp, which will contribute to the development of new type CpG ODN adjuvant in aquaculture industry.